AN ANALYSIS OF MACROECONOMIC INDICATORS ON EXCHANGE RATES IN INDONESIA - Raka Putri Agfial; Benny Budiawan Tjandrasa (ZILLZELL MEDIA PRIMA, 2024)
Elections represent a significant political event in Indonesia, often leading to fluctuations in the financial sector. The impact of these fluctuations can be observed through the trends in the Composite Stock Price Index (IHSG) and the exchange rate during presidential election periods. Historical data from presidential elections between 2009 and 2019 indicates a consistent increase in both the IHSG and the exchange rate. However, the 2024 presidential election presents an unusual scenario where the IHSG shows a strengthening trend leading up to the election, while the Indonesian rupiah remains weak against foreign currencies, particularly the USD. Following a decline in the IHSG, the rupiah experienced a sharp drop. Consequently, this study aims to elucidate the determinants of the exchange rate by examining several macroeconomic variables, including Gross Domestic Product (GDP), global oil prices, the budget deficit, foreign direct investment, inflation, and interest rates. Utilizing time series data from 1991 to 2023 in Indonesia and employing multiple linear regression analysis, the research identifies that global oil prices significantly influence the exchange rate by positively moderating the effect of GDP. Additionally, interest rates are found to have a significant negative impact on the exchange rate.